Protection of horse chestnut (Aesculus hippocastanum L.) in an urbanized environment - Bashchenko, M.; Shita, O.; Fedorenko, A.; Chaika, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. Justification of the protection of the common bitter chestnut in the conditions of an urbanized environment. Methods. In 2023—2024, a literature analysis of the protection of the common bitter chestnut (Aesculus hippocastanum L.) from the pest of the chestnut moth (Cameraria ohridella D.) was carried out in the laboratory of pesticide application technology of the IPP of NAAS. In the Hryshka Botanical Garden, a visual examination of the crown and leaves of Aesculus hippocastanum was carried out on 15 trees in order to detect insects, in particular Cameraria ohridella and entomophages. Yellow and green colored glue traps were used to determine the presence of Cameraria ohridella. Recordings were carried out at intervals of 1 time every 10 days after the start of the flight of Cameraria ohridella. The search for entomophages was carried out in accordance with established methods. Processing of the obtained data was performed according to standard methods. Results. Studies show that the protection of Aesculus hippocastanum is based on the use of mechanical, chemical and biological methods. Monitoring of the seasonal dynamics of the population of Cameraria ohridella and control of its population was carried out using colored glue traps during the growing season. Colored traps have been found to be highly effective in reducing Cameraria ohridella, although they are not without some drawbacks. In 2023, 1.755 copies were recorded on the yellow trap. insects, of which 91.4% were Cameraria ohridella butterflies, while 8.6% were endoparasites of the species Pediobius saulius W. 1434 insects were caught on the green trap, among which 85.3% were Cameraria ohridella, and 14.7% were Pediobius saulius W. In 2024, 1.652 insects were recorded on the yellow trap, of which 80.9% were Cameraria ohridella, and 19.1% were endoparasites. 1185 insects were recorded on the green trap, of which 81.8% were Cameraria ohridella, and 18.2% were endoparasites. On the territory of the botanical garden named after the following were found: Formica rufa, Meconema thalassinum, Pediobius saulius, as well as the presence of Parus sp. birds, which can affect the number of Cameraria ohridella. Conclusions. To control the number of Cameraria ohridella in the urban environment, it is necessary to use mechanical, chemical and biological methods. These include: the use of colored glue traps (green and yellow); collecting and disposing of fallen leaves; apply injections into the tree trunk, starting with a diameter of 45 cm. To protect young Aesculus hippocastanum trees (tree diameter less than 45 cm), it is advisable to increase the number of nests to attract birds; carry out a mass release of the endoparasite Pediobius saulius Walker; use actrancanths to attract Pediobius saulius Walker and Meconema thalassinum.